Association of breastfeeding and postmenopausal osteoporosis in Chinese women: a community-based retrospective study - Guiming Yan; Yaqi Huang; Hong Cao; Jie Wu; Nan Jiang; Xiaona Cao (BMC, 2019)
Abstract Background Postmenopausal osteoporosis (PMOP) has long been a pervasive public health concern. With the aging Chinese population, the prevention, assessment and management of postmenopausal osteoporosis were particularly important. During the breastfeeding, a large amount of Calcium loss from maternal bone for infants' growth. However, whether this loss is completely reversible remains controversial. As the relationship between breastfeeding and postmenopausal osteoporosis is different from society to society and is not clear from the literature, the purpose of this study was to determine whether breastfeeding was an independent factor for the development of PMOP based on Chinese postmenopausal population. Methods A retrospective cross-sectional investigation was conducted at Tianjin Xiaobailou health Community Healthcare Center between December 2017 and June 2018. Postmenopausal women over the age of 50 who underwent the annual health examination or visited the center to perform bone densitometry as a part of routine screening for disease were recruited. A trained community nurse administered a questionnaire to all participants by face-to-face interview. Participants were questioned about age, BMI, Vitamin D and calcium intake, the history of smoking, drinking and fracture, age of menarche, age of menopause, the number of pregnancy, parity, feeding pattern (breastfeeding, artificial feeding and mixed feeding) and overall breastfeeding duration. BMD measurements were carried out using quantitative ultrasound (QUS) at the bilateral radius. Results A total of 202 women who met the inclusive and exclusive criteria were enrolled. Univariate analysis revealed that overall breastfeeding more than 24 months increased the risk of osteoporosis (OR 39.00, 95%CI 2.40-634.65, p = 0.010). However, multivariate estimate of the risk of osteoporosis by overall breastfeeding duration suggested that when controlling for age, BMI, the number of pregnancy and parity, the overall breastfeeding duration was not an independent risk factor for postmenopausal osteoporosis (OR 5.22, 95%CI 0.18-147.76, p = 0.333). Additionally, age (OR 1.16, 95%CI 1.05-1.29, p = 0.003), BMI (OR 1.26, 95%CI 1.04-1.54, p = 0.021) and the number of pregnancy (OR 1.80, 95%CI 1.08-2.98, p = 0.024) were significant associated with postmenopausal osteoporosis. Conclusion Breastfeeding was not associated with postmenopausal osteoporosis, while age, BMI and the number of pregnancy may contribute to increasing risk of postmenopausal osteoporosis in Chinese women.